'Mind the (Skills) Gap': Micro-credentials in the Skills Development Toolkit of Employers and Industrial Ecosystems (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2026)
In a world of fast-evolving upskilling and reskilling needs, micro-credentials have been gaining momentum as agile and complementary ways of acquiring, certifying, and making skills and competences visible. Recognizing their potential, many countries are exploring or have started integrating micro-credentials into their national qualifications frameworks, facilitating transparency, trust, portability, and alignment with existing education and training systems. The recognition of micro-credentials, however, still shows inconsistencies in these formal systems. Combining micro-credentials with open recognition principles can unlock untapped potential at the workplace, a key space where skills and competences are applied. A primary attraction of micro-credentials, and similar short forms of learning, is that they can be tailored for specific skills requirements. They are also quicker to develop and deploy, smaller in size, and have the flexibility to fit around the schedule of professionals. Developing a culture of recognition provides context and ensures visibility and esteem for the skills and competences in the workplace and in the broader industry. The combination of the two offers employers an intriguing way to develop a competitive advantage, attract, and retain talent, and address skills gaps amid rapid digital transformations.  These powerful forces increasingly position employers as drivers of micro-credential development, which is evidenced by the growing number of provider and industry partnerships in this space. There is scope, however, for employers to take an even more active role across the life-cycle, going from design through recognition to championing micro-credentials. What does such an active role look like in practice? What support structures can facilitate industry and employer engagement, offering an entry point and a community to deepen practices? What makes a community of practice effective? This presentation explored various European-funded projects, national-level initiatives, European initiatives, and flagship actions supporting the Union of Skills to provide food for thought in this space. Examples will include thematic, industry-driven collaborative structures for up- and reskilling, such as the Large-Scale Partnerships within the Pact for Skills. These multi-stakeholder and multi-country communities of practice are dedicated to strengthening collective action on skills development for their respective industrial ecosystems. Focusing on joint actions for the green and digital transitions, individual Large-Scale Partnerships define up-and reskilling commitments across their industries that incorporate multiple approaches, including micro-credentials. The presentation also included initiatives that are education provider-driven, such as the European University Alliances, contrasting these approaches. With 65 such Alliances encompassing more than 570 higher education institutions of all types and from across Europe, the EUAs are a significant strategic development in the European Higher Education Area (EHEA). The presentation reflected on thematically focused Alliances of Technological Universities or Universities of Applied Sciences where close industry collaborations are at the core of institutional and Alliance missions. To offer complementary perspectives,  national initiatives, such as the Skillnet Ireland network, were also highlighted. Focusing on talent development, the 70 thematic or region-focused private-sector Skillnet Business Networks across Ireland are hives of activity addressing skills needs and providing upskilling and reskilling programs. A national agency of Ireland, Skillnet Ireland provides a vehicle for highly focused industry, education, and training sector collaborations. Concentrating mainly on European and some national-level examples, the presentation also examined how such macro-level practices can provide spill-over effects for developing employer-level approaches. Keywords: micro-credentials, industry ecosystems, European initiatives, communities of practice